Prevalence of delusional ideation in a district in southwestern Uganda - Lundberg, Patric; Cantor-Graae, Elizabeth; Kabakyenga, Jerome; Rukundo, Godfrey; Stergren, Per-Olof O¨ (Elsevier Ltd, 2004)
Background: Population-based prevalence studies suggest that psychosis is a continuum distributed in the general population. Aim: To assess the prevalence of delusional ideation in young healthy individuals in a low-income country setting (Uganda) and to investigate possible relevant background factors. Method: Interviews were conducted in a district capital and in three rural villages, using the Peters et al. Delusions Inventory (PDI-21). Results: Levels of delusional ideation and associated levels of distress, preoccupation, and conviction were higher than in studies conducted in Europe. Higher PDI-21 scores were associated with younger age and with urban residence. The urban effect was stronger in persons with a higher level of education. Conclusions: Although the factors that contribute to population differences in levels of delusional ideation are currently unknown, the results suggest that urban residence may be an important influence.
Keywords: Delusional ideation; PDI; Schizophrenia; Urbanicity; Uganda